2022
DOI: 10.1109/access.2022.3175978
|View full text |Cite
|
Sign up to set email alerts
|

Land Cover Classification of Resources Survey Remote Sensing Images Based on Segmentation Model

Abstract: Land type survey is an important task of land resources survey and the basis of scientific management of land resources. With the increasingly prominent problems of population, resources, and environment, there is an urgent need for a fast and accurate classification method of large-scale land use and land cover based on remote sensing data. Traditional machine learning classification methods based on pixel classification achieved sufficient results and are widely used, such as maximum likelihood classificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 54 publications
0
5
0
1
Order By: Relevance
“…Moreso, several studies have implemented works for very high RS images. However, only few studies have focused on low and medium-resolution images [70,80,117,156]. As future insight, it is recommended to conduct more research using fast and efficient DL methods for low and medium resolution RS.…”
Section: Analysis Of Rs Imagesmentioning
confidence: 99%
“…Moreso, several studies have implemented works for very high RS images. However, only few studies have focused on low and medium-resolution images [70,80,117,156]. As future insight, it is recommended to conduct more research using fast and efficient DL methods for low and medium resolution RS.…”
Section: Analysis Of Rs Imagesmentioning
confidence: 99%
“…T HANKS to the rapid development of aerospace technology, it is easier to acquire high-resolution remote sensing images with more detailed land surface information, which can support finer classification and increase the diversity of remote sensing applications, but how to effectively acquire the information contained in high-resolution remote sensing images has become an urgent problem to be solved. Land cover classification as a decoding method has gradually become an important task in high-resolution remote sensing image processing, and has wide applications in land-use planning [1], [2], environmental monitoring and protection [3], [4],…”
Section: Introductionmentioning
confidence: 99%
“…Unlike traditional machine learning classification methods, deep learning models exhibit the unique ability to automatically extract features and learn complex patterns from input features, thereby alleviating the necessity for extensive variable training. Numerous studies have demonstrated the superior performance of deep learning models over traditional ML methods in remote sensing applications [22][23][24]. Among state-of-the-art models, the U-Net segmentation model and artificial neural networks (ANNs) have consistently demonstrated superior performance in remote sensing image analysis [25][26][27].…”
Section: Introductionmentioning
confidence: 99%